GENERAL FOUNDATIONS OF PEDAGOGICAL TECHNOLOGY IN THE HIGHER EDUCATION SYSTEM - Khalikov Abdulxak; Musamedova Kamola (Scholar Express Journal, 2021)
The work examines the problematic issues of modern pedagogical technology in the pedagogical education system, the goals, objectives of education and upbringing, which guarantees the availability of pedagogical technology for higher education, touches upon some aspects of pedagogical skills associated with the practical implementation of the technological process inherent in pedagogy. It is shown that pedagogical technology has a scientific character and it is necessary to recognize that it has a practical orientation that can be used in solving specific issues.
Keywords: Pedagogical technology; teacher skill; pedagogical education system